Thermal expansion flow analysis in designing a sustainability computer personal unit casing - Sahroni, T.R.; Ahmad, Saifol Anuar; Akmal, Suriati (2023)
The material of computer personal unit is commonly used metal based. The problem occurs when waste of electronic device to be recycled. This paper describes the thermal expansion flow in designing a sustainability computer personal unit (CPU) casing based on the material selection technique. In this study, the design concepts were generated to be processed for screening matrix with criteria selection of comfortable, user friendly, ergonomic, flexible, functionality and material. Design concept 4 was selected to be further analyzed. The material selection technique was used in this study using CES Edupack and provide the material of Acrylonitrile butadiene styrene (ABS), Polyetheretherketone (PEEK), and Polyoxymethylene (Acetal, POM) for analysis based on criteria of recycle ability, price, hardness, density, and temperature maximum. The ABS material suits the design requirement toward sustainability computer personal unit. Based on the simulation result, the thermal expansion flow meets the design specification. In addition, the phenomena of heat dissipated from internal CPU shows significant information for design manufacturing to manage and place the electronic parts properly to reduce the risk of overheated and damaged.